Efektivitas, Pemanfaatan Teknologi dan Kemudahan Dalam Penerapan Sistem Informasi Akuntansi (Studi Pada Rumah Sakit Islam Jakarta) - Nurul Karima; Masagus Asaari (Lembaga Penelitian Universitas YARSI, 2019)
The purpose of this study was to determine the effect of effectiveness, use of technology and ease in the application of accounting information systems on employee performance at Jakarta Islamic Hospital. This type of quantitative research, data collection techniques using a questionnaire, the study sample was 43 employees of the accounting information system division, sampling techniques using saturated samples. Data analysis techniques used multiple linear regression analysis, coefficient of determination, hypothesis testing partially and simultaneously. The results showed that the effectiveness, utilization and ease in the application of accounting information systems had partially and simultaneously a positive effect partially and simultaneously, and also this positive effect was significantly on the performance of employees of Jakarta Islamic Hospital. The coefficient of determination obtained 93.2%, this result means the magnitude of the effectivity of effectiveness (X1), utilization (X2) and ease (X3) in the application of accounting information systems simultaneously on the performance of employees of the Islamic Hospital of Jakarta (Y) is 93.2%, while the rest is 6.8% is influenced by other factors.